Improving the understanding of central Bohai Sea eutrophication based on wintertime dissolved inorganic nutrient budgets: Roles of north Yellow Sea water intrusion and atmospheric nitrogen deposition. (December 2020) - Zheng, Li-wen; Zhai, Wei-dong; Wang, Li-fang; Huang, Tao
Abstract: The Bohai Sea is a shallow-water, semi-enclosed marginal sea of the Northwest Pacific. Since the late 1990s, it has suffered from nutrient over-enrichment. To better understand the eutrophication characteristics of this important coastal sea, we examined four survey datasets from summer (June 2011), late autumn (November 2011), winter (January 2016), and early spring (April 2018). Nutrient conditions in the Bohai Sea were subject to seasonal and regional variations. Survey-averaged N/P ratios in estuarine and nearshore areas were 20–133. In contrast, the central Bohai Sea had mean N/P ratios of 16.9 ± 3.4 in late autumn, 16.1 ± 3.0 in winter and 13.5 ± 5.8 in early spring, which are close to the traditional N:P Redfield ratio of 16. In summer, both dissolved inorganic nitrogen (DIN) and dissolved inorganic phosphate (DIP) were used up in the surface waters of the central Bohai Sea, suggesting that the biological consumption of DIN and DIP may also follow the Redfield ratio. Wintertime nutrient budgets of the central Bohai Sea water were then established based on a mass balance study. Our results suggest that the adjacent North Yellow Sea supplied additional DIP to the central Bohai Sea via wintertime water intrusion, balancing terrigenous excess DIN that was introduced in summer. A water-mixing simulation combining these two nutrient sources with atmospheric nitrogen deposition suggests that eutrophication in the central Bohai Sea will likely be enhanced by the large-scale accumulation of anthropogenic nitrogen in adjacent open oceans. Such changes in nutrients may have fundamentally contributed to the recent development of algal blooms and seasonal hypoxia in the central Bohai Sea. Graphical abstract: Image 1 Highlights: Wintertime DIN/DIP ratios in the central Bohai Sea were around 16 in the 2010s. The adjacent Yellow Sea supplies additional phosphate to the Bohai Sea in winter. Eutrophication in the central Bohai Sea is connected to regional nutrient changes. Abstract : Capsule : The nutrient element ratio and eutrophication status of the Bohai Sea were characterized and explained using newly obtained data.